GENESIS, DEVELOPMENT, AND CLASSIFICATION FOR SOME SELECTED SOILS AT KURDISTAN REGION, NORTH OF IRAQ - Fayyadh, M. A.; Ismail, H. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The study area was located in the North of Iraq. Five sites were selected that have formed from the limestone parent material. One pedon dug in each site and was divided into a number of horizons. Thirty-five soil samples were collected for physical and chemical analyses. The climate of study sites were similar to the Mediterranean Sea climate which is hot dry in summer and cool humid in winter. The mean of annual precipitation, varies from one site to another. Studied soils classified as Mollisols, Inceptisols, Vertisols, and Aridisols. Study soils were relatively high clay content and its content at the surface horizons is lower than it at subsurface horizons, and soil texture was ranged between clayey to loamy, the high value for clay content indicates to soil development. Fine clay/Coarse clay ratio showed that the pathway of fine clay similar to the pathway of total clay. CEC values increased with increasing clay. Organic matter was high in the surface horizons and decrease with depth. The following pedogenic processes occurred in study soils loss, gain, leaching, illuviation, eluviation, alkalization, humification, lessivage, desalinization, calcification, decomposition, and synthesis.